2019
DOI: 10.31223/osf.io/ftwgm
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection Uncertainty Matters for Understanding Atmospheric Rivers

Abstract: The 3rd ARTMIP WorkshopWhat: Over 30 participants from multiple universities and research insititutionsmet to discuss new results from the Atmospheric River TrackingMethod Intercomparison Project.Where: Lawrence Berkeley National Lab, Berkeley, CA, USAWhen: 16-18 October 2019

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 10 publications
0
25
0
Order By: Relevance
“…Our second major improvement responds to the call by the third ARTMIP workshop (Brien et al, 2020) to identify different “flavors” of ARs that are controlled by diverse physical mechanisms and weather systems, such as subtropical high, subpolar low, TC‐like features, ECs, monsoon, and localized perturbation (Hu et al, 2017; Kamae, Mei, Xie, Naoi, & Ueda, 2017; Xiong et al, 2019; Zhang et al, 2018). Our experience strongly suggest that one AR event might possess multiple “flavors” carried by different AR segments, that is, one AR event might encounter a number of systems that modify its segmental geometric and dynamic features.…”
Section: Panlu20 and Ea Ar Catalogmentioning
confidence: 90%
See 1 more Smart Citation
“…Our second major improvement responds to the call by the third ARTMIP workshop (Brien et al, 2020) to identify different “flavors” of ARs that are controlled by diverse physical mechanisms and weather systems, such as subtropical high, subpolar low, TC‐like features, ECs, monsoon, and localized perturbation (Hu et al, 2017; Kamae, Mei, Xie, Naoi, & Ueda, 2017; Xiong et al, 2019; Zhang et al, 2018). Our experience strongly suggest that one AR event might possess multiple “flavors” carried by different AR segments, that is, one AR event might encounter a number of systems that modify its segmental geometric and dynamic features.…”
Section: Panlu20 and Ea Ar Catalogmentioning
confidence: 90%
“…First, notwithstanding some progress in distinguishing TC‐like features (Mundhenk et al, 2016; Pan & Lu, 2019), failures are still reported when the TC‐like feature occurs as a partition of AR. Second, a robust method distinguishing TMFs from ARs is still lacking, which is critical for studies covering the tropics (Brien et al, 2020). Third, as a large‐scale phenomenon, partitions of an AR are likely affected by different systems and processes (e.g., monsoon, extratropical cyclones [ECs], TC‐like features, and localized perturbation) and have distinct features (e.g., varying IVT intensity and IVT coherence), especially for ARs with varying shape, orientation, and curvature.…”
Section: Introductionmentioning
confidence: 99%
“…The American Meteorological Society (AMS) definition for AR contains little quantitative guidance (AMS, 2019), allowing for flexibility in ARDT development but also contributing to differences across ARDTs. These differences, which include variations in terms of detection variable (e.g., IWV and IVT), thresholds on the intensity of detection variables, geometry, event persistence, and/or other detection considerations, can ultimately affect conclusions about AR characteristics and impacts (O'Brien et al, 2020; Payne et al, 2020; Rutz et al, 2019; Shields et al, 2018). While some ARDTs rely on relative moisture thresholds derived from climatology (e.g., Guan & Waliser, 2015; Lavers et al, 2012), others use absolute thresholds for either IWV (Ralph et al, 2004; Wick et al, 2013) or IVT (Equation ) (Leung & Qian, 2009; Rutz et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Studies based on ARTMIP have started to explore uncertainty with respect to AR detection, and the uncertainty is larger than many in the community had anticipated (Shields et al, 2018(Shields et al, , 2019bChen et al, 2018;Rutz et al, 2019;Shields et al, 2019a;Chen et al, 2019;Ralph et al, 2019b;Payne et al, 2020). Preliminary results from the ARTMIP Tier 2 experiments suggest that AR detection uncertainty may be comparable to model uncertainty in future climate simulations (O'Brien et al, 2020b), which implies that ongoing AR research would benefit from consideration of AR detection uncertainty. TECA BARD v1.0.1 offers an efficient way for future studies to quantify AR detection uncertainty in situ.…”
Section: The Importance Of Uncertainty In Feature Detectionmentioning
confidence: 99%